2006
DOI: 10.1021/jp056148s
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Studies of the Size, Shape, and Internal Structure of 0% and 90% Acetylated Fifth-Generation Polyamidoamine Dendrimers in Water and Methanol

Abstract: We have performed molecular dynamics simulations of 0% and 90%-acetylated G5 PAMAM dendrimers in water and methanol and obtained radii of gyration of 2.51~2.57nm and 2.11~2.33nm, respectively, similar to those measured experimentally in methanol by Prosa et al. (J. Polymer. Sci. 35, 2913-2924 and in water by Choi et al. (Nano Letters,4,[391][392][393][394][395][396][397]. Calculation of the moments of inertia and the relative shape anisotropy show that both 0% and 90%-acetylated G5 are modestly ellipsoidal. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
102
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(113 citation statements)
references
References 29 publications
10
102
1
Order By: Relevance
“…Thus, these simulations are routinely used to investigate conformational changes of a single dendrimer in explicit solvent with respect to dendrimer generation (size) and process conditions, such as temperature and solvent pH [52][53][54][55]62,63]. All-atom simulations may also be used to investigate the dynamics of binding between of a single dendrimer and one or more ligands in explicit solvent [24,38,39,64].…”
Section: All-atom Molecular Dynamics Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, these simulations are routinely used to investigate conformational changes of a single dendrimer in explicit solvent with respect to dendrimer generation (size) and process conditions, such as temperature and solvent pH [52][53][54][55]62,63]. All-atom simulations may also be used to investigate the dynamics of binding between of a single dendrimer and one or more ligands in explicit solvent [24,38,39,64].…”
Section: All-atom Molecular Dynamics Simulationsmentioning
confidence: 99%
“…As with all applications of molecular simulation, selecting an appropriate force field for modeling dendrimers and dendrimer-ligand complexes is critical to obtaining the correct fundamental behavior. In the case of PAMAM dendrimers, it has been frequently shown that predictions from molecular simulation for the swelling behavior of dendrimers as a function of solvent pH and salt concentration are very sensitive to the force field used in those simulations [52][53][54]. The hydrogen bonding parameters in the Dreiding III force field were recently optimized to prevent the swelling of PAMAM dendrimers at low pH and to predict radii of gyration that are consistent with small-angle neutron scattering experiments [63].…”
Section: All-atom Force Fields For Modeling Dendrimersmentioning
confidence: 99%
“…Molecular dynamics studies of PAMAM dendrimers have already helped to elucidate the structural features and behavior of these molecules. A study varying the percentage acylation of a generation 5 PAMAM dendrimer showed that their overall shape was not dependent upon the percentage of acyl groups on their surface because intramolecular hydrogen bonds form and break during the simulation [10].…”
Section: Introductionmentioning
confidence: 99%
“…The images were rendered using VMD [25]. consistent with previous experimental [23,24,26] and theoretical [20,[27][28][29][30] characterization of PAMAM in solution.…”
Section: Resultsmentioning
confidence: 99%